PENDAMPINGAN PEMANTAPAN MATERI OLIMPIADE RUMPUN PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH NEGERI (MAN) 3 KEDIRI - Muhammad Zamroji; Zainal Fanani; Achmad Nur; Baihaki, Imam (Al Busyro : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Mentoring Program for Islamic Education Olympiad Material Preparation at Madrasah Aliyah Negeri (MAN) 3 Kediri is an initiative aimed at enhancing students' competencies for participating in Islamic Education (PAI) Olympiads at regional and national levels. This program is designed to provide intensive guidance and material reinforcement across key areas within the PAI discipline, including Aqidah Akhlak (Islamic Belief and Morals), Fiqh (Islamic Jurisprudence), Al-Qur'an Hadith, and Islamic Cultural History. Through specialized mentoring by experienced teachers and coaches, students are trained to deeply understand core concepts, strengthen analytical abilities, and improve their skills in answering Olympiad questions. The program uses a structured learning approach, ranging from fundamental material review to exam simulations aligned with Olympiad formats. The outcomes of this program are expected to equip students with confidence and a solid understanding, enabling them to excel in competitive settings. Furthermore, this program contributes to improving the quality of education at MAN 3 Kediri and fosters the development of religious character, critical thinking, and a positive competitive spirit among students